Evaluation of Bulk Fill Composite Roughness Polished with Spiral Rubber Discs: An In-vitro Study - Silva, Glaucia Danielle Ferreira da; Dias, Marlon Ferreira [UNESP]; Lins, Claudio Eufrasio Medeiros; Siqueira, Eric Roberto Soares Xavier de; Cahu, Amina Kadja Martins; Oliveira, Natalia Gomes de; Almeida, Renata Albuquerque Cavalcanti; Espindola-Castro, Luis Felipe (Premchand Shantidevi Research Foundation, 2022)
Introduction: Restorations with high surface roughness directly influences restorative procedure longevity. When used correctly, polishing systems optimizes the quality, aesthetics and longevity of composite resins. Aim: To evaluate the influence of three two-step polishing systems of spiral rubber discs on surface roughness of three different bulks fill composite resins. Materials and Methods: This in-vitro study was conducted from May, 2021 to January 2022, at the Universidade Estadual de Pernambuco, School of Dentistry, Recife, Pernambuco, Brazil. Total 20 specimens of each resin {three Bulk Fill resins: Filtek One Bulk Fill (3M-ESPE), Aura Ultra Universal Restorative Bulk Fill (SDI) and Opus Bulk Fill (FGM)} were randomly divided into four groups (n=5 each). The three groups include test polishing systems {Sof-Lex Diamond Polishing System (3M/ESPE, Saint Paul, Minnesota, USA), Decamp Plus Twist Spiral EVE (Odon omega, Ribera Prato, SP, Brazil), Spiral Swivel (Jota, Ruth, Kanton St. Gallen, Switzerland)} and one control group include no polishing system. To assess surface roughness, before and after polishing, specimens were evaluated on a digital rugosimeter. Data was subjected to the Shapiro-Wilk test to assess normality, followed by Analysis of Variance (ANOVA) to compare the mean between the different types of resins and types of polishers. Results: For the composite resins studied, significant differences were observed only when polished with Soflex Spiral (p-value=0.013). All polishing system caused a significant improvement in the roughness of composite resins compared to the control group. The mean roughness reduction comparison test between the types of polisher was significant (p-value <0.001), there was a significantly greater reduction in the roughness of EVE Decamp Plus Twist Spiral and Swivel Spiral polish system, compared to polish system from Sof-Lex Diamond Polishing System and control group. No statistically significant differences were found between EVE Diacomp Plus Spiral and Spiral Swivel polishing system. Conclusion: The spiral rubber polishers evaluated were effective in reducing the roughness of bulk fill composites. However, EVE Decamp Plus Spiral and Spiral Swivel polishers showed better results than Sof-Lex Spiral.
Keywords: Composite Resins; Dental Aesthetic; Dental Polishing